Characterization of alumina-magnesia-carbon refractory bricks containing aluminium and silicon. Issue 8 (1st June 2018) - Calvo, W.A.; Ortega, P.; Velasco, M.J.; Muñoz, V.; Pena, P.; Martinez, A.G. Tomba
Abstract: The present paper is a continuation of previous ones focused on the characterization of alumina-magnesia-carbon refractories (AMC) bricks. Unlike those characterised materials which only have aluminium as an antioxidant, a brick also containing silicon is comparatively analysed in this paper. Along with metallic aluminium, silicon is among the most commonly used antioxidant additives in oxide-C refractories, but the studies on the incorporation of this metal into AMC bricks are rather limited. In this work, several complementary techniques were used in combination to achieve a detailed characterization in relation to the physical and chemical characteristics and thermal evolution of the Si-containing AMC refractory: X-ray fluorescence, plasma emission spectroscopy, gravimetry, granulometry, X-ray diffraction, differential thermal and thermogravimetric analyses, reflection optical and scanning electron microscopies, mercury intrusion porosimetry, and density, porosity, permanent linear change and permeability measurements. In addition, the characterization was completed by evaluating the chemical resistance to air and to a basic slag and calculating the equilibrium composition of the brick when it is subjected to high temperatures (up to 1400 °C). A comparison with the results obtained for previously characterised AMC bricks with similar MgO contents and metallic aluminium as an antioxidant was also made. The presence of silicon was related to finer open porosity and higher oxidation resistance at high temperature (1400 °C).